Outcome of pregnancy among high risk pregnancies in rural area of Nagpur, Central India - Jadhao, Ashok Rupraoji; Gawade, Mahendra D.; Ughade, Suresh N. (International Journal Of Community Medicine And Public Health, 2017)
Background: All pregnant women, by virtue of their pregnancy status, face some level of maternal risk. Some pregnancies are complicated by problems associated with mother’s health. Most maternal morbidities could be prevented if mother had access to appropriate and timely healthcare during pregnancy. Study was intended to find out prevalence of high risk pregnancy and pregnancy outcome among them in rural area of Nagpur district, Central India. Methods: Community based observational descriptive study was conducted on consecutive sample of 214 pregnant women, who had 20 weeks and above gestational period. Results: Prevalence of high risk pregnancy observed was 33.64% (95% CI 27.31%-39.97%). Caesarean section (OR=7.63, 95% CI=4.04-14.40, P=0.0001) and birth weight less than 2500gm (OR= 3.47, 95% CI=1.47-8.20, P=0.003) were significantly associated with high risk pregnancy. Mode of delivery caesarean section had strong relationship with previous history of caesarean section (OR=37.53, 95% CI=8.64-163.05, P=0.0001) and mothers height less than or equal to 140cm (OR=8.87, 95% CI=1.02-77.32, P = 0.0183). Pregnancy outcome low birth weight was significantly associated with oligohyramnios (OR = 8.45, 95 % CI=1.61-44.48, P=0.003) and history of caesarean section (OR=2.67, 95 % CI=1.01-7.07, P = 0.041). Conclusions: Prevalence of high risk pregnancy was almost one-third in pregnant women in rural area of central India. Mode of delivery caesarean section and birth weight less than 2500gm was significantly associated with high risk pregnancy. History of caesarean section and height less than or equal to 140 cm influence the outcome of pregnancy i.e. caesarean section. Birth weight, LBW (Low Birth Weight) was associated with history of caesarean section and oligohyramnios.